The effect of chilling on the photosynthetic activity in coffee (Coffea arabica L.) seedlings. The protective action of chloroplastid pigments - Oliveira, Jurandi Gonçalves de; Alves, Pedro Luis C. A.; Magalhães, Antonio Celso (FapUNIFESP (SciELO), 2002)
Coffea arabica is considered to be sensitive to low temperatures, being affected throughout its entire life cycle. Injury caused by chilling (low temperatures above zero degree centigrade) is characterized primarily by inhibition of the photosynthetic process. The objective of this work was to evaluate the role of photosynthetic pigments in the tolerance of coffee (C. arabica L.) seedlings to chilling. The evaluation the photosynthetic activity was made by emission of Chl a fluorescence at room temperature (25°C) in vivo and in situ, using a portable fluorometer. The pigment content was obtained by extraction with 80% acetone, while estimation of membrane lipid peroxidation was determined by measuring the MDA content in leaf tissue extracts. The results indicated a generalized reduction in the quantum yield of PSII when the seedlings were maintained in the dark. The reduction occurred in the seedlings submitted to chilling treatment as well as in the control ones. This demonstrates that not only chilling acts to cause an alteration in PSII. It is possible that the tissue storage reserves had been totally exhausted, with the respiratory rate exceeding the photosynthetic rate; the later was nil, since the seedlings were kept in the dark. The efficiency in the capture, transfer and utilization of light energy in PS11 photochemical reactions requires a sequence of photochemical, biochemical and biophysical events which depend on the structural integrity of the photosynthetic apparatus. However, this efficiency was found to be related to the protective action of chloroplastid pigments, rather than to the concentration of these pigments.
Keywords: Chlorophyll a fluorescence; Coffee; Lipid peroxidation; Photosynthetic pigments; Coffea arabica